2015
DOI: 10.1242/jcs.166249
|View full text |Cite
|
Sign up to set email alerts
|

The myelin proteolipid plasmolipin forms oligomers and induces liquid-ordered membranes in the Golgi complex

Abstract: Myelin comprises a compactly stacked massive surface area of protein-poor thick membrane that insulates axons to allow fast signal propagation. Increasing levels of the myelin protein plasmolipin (PLLP) were correlated with post-natal myelination; however, its function is unknown. Here, the intracellular localization and dynamics of PLLP were characterized in primary glial and cultured cells using fluorescently labeled PLLP and antibodies against PLLP. PLLP localized to and recycled between the plasma membrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…The MARVEL domain has been shown to be involved in cellular events such as vesicular transport and junction regulation 52 . PLLP function is not well-characterised, however it has been found to form cation-specific ion channels 53 , 54 , promote myelin synthesis, regulate polarised epithelial differentiation, tight junction formation and epithelial cell differentiation 51 , 55 . In addition, PLLP regulates zebrafish intestinal epithelial cell differentiation by regulating Notch signaling, and mutation of pllp reduces Notch1 expression 51 .…”
Section: Discussionmentioning
confidence: 99%
“…The MARVEL domain has been shown to be involved in cellular events such as vesicular transport and junction regulation 52 . PLLP function is not well-characterised, however it has been found to form cation-specific ion channels 53 , 54 , promote myelin synthesis, regulate polarised epithelial differentiation, tight junction formation and epithelial cell differentiation 51 , 55 . In addition, PLLP regulates zebrafish intestinal epithelial cell differentiation by regulating Notch signaling, and mutation of pllp reduces Notch1 expression 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that fuelling neurons and supporting the integrity of myelinated axons during extended wake occur at the cost of myelin thinning. This would be in line with the fact that the transcript coding for plasmolipin, which helps assemble potential myelin membrane precursor domains at the Golgi complex (Yaffe et al, ) has been repeatedly found to be downregulated in sleep deprivation experiments (Cirelli et al, ; Mongrain et al, ; Bellesi et al, ).…”
Section: Sleep and Myelinmentioning
confidence: 62%
“…Of note, both Opalin and Plasmolipin were found upregulated in sleep also by other studies (Cirelli et al, ; Mongrain et al, ). Opalin is thought to help myelin stabilization at the paranodal region (Yoshikawa et al, ), while Plasmolipin participates in the biogenesis of myelin by forming membrane domains at the Golgi complex thanks to its capacity of attracting cholesterol and sphingolipids (Yaffe et al, ). Finally, Qk codes for an RNA‐binding protein that posttranscriptionally regulates mRNA stability and distribution of several myelin‐associated transcripts, including Mbp and Mag (Zearfoss et al, ).…”
Section: Sleep and Myelinmentioning
confidence: 99%
“…In contrast, a number of genes involved in lipid metabolism and in particular in glycerophospholipid biosynthesis-Dgat2, Cds1, Elovl7, Chka-as well as in myelination-Opalin, Pllp, Qk-were transcribed preferentially during sleep [11]. Opalin is thought to be important for myelin stabilization at the paranodal site [12], whereas plasmolipin participates in the biogenesis of myelin by forming membrane domains at the Golgi level [13]. Qk regulates several myelinrelated transcripts (i.e.…”
Section: Introductionmentioning
confidence: 99%